Impact of aquaculture feed technology on fish income and poverty in Kenya. Issue 4 (2nd October 2018) - Amankwah, Akuffo; Quagrainie, Kwamena K.; Preckel, Paul V.
ABSTRACT: The impacts of improved agricultural technologies on smallholder households in Africa are well documented in the literature. However, the literature on the welfare impacts of aquaculture technologies, especially in the context of smallholder households, is very scanty. This paper applies the propensity score matching technique to household survey data to examine the impact of improved feed technology on fish income and poverty in Kenya. After controlling for observable household characteristics, the results indicate that improved feed technology increases aquaculture income and reduces poverty among fish farming households. Specifically, the income effect of the technology is 23–37%, with resultant poverty reduction effect of 19–23% points. Evidence from the study indicates that the likelihood of adopting improved feed in Kenya will surge with improved extension service delivery, access to government subsidized feed, and easy market access for purchasing improved feed and sale of mature fish.